Knowledge, Attitude and Perception of Oral Diseases Presented by the Patients to General Medicine Practitioners in the Suburban areas of Nagpur City.: Life Sciences-Periodontitis for Dental health - Talatule, Dhiran; Ramhari; Gaikwad, Romita; Lanjekar, Ashish; Kulkarni, Sunita; Chandak, Rakhi (International Journal of Life Science and Pharma Research, 2021)
General Medicine Practitioners (GPs) are often the first point of contact for advice and management in cases of dental related pain. The reasons for presentation to the General Practitioners, rather than the dentist, include non-classic presentation of dento-facial pain, lack of coordinated after hours dental care, poor patient education, patients’ prescription of their GP as the primary coordinator of integrated total health care and financial considerations. This study aims to assess the knowledge, attitude and awareness of the common oral diseases and to create awareness of the prevailing dental conditions among general practitioners, techniques for better diagnosis, and appropriate management protocols for different dental conditions.A questionnaire study was carried out among 130 General Practitioners in the suburban areas of Nagpur City using an online survey tool. 21 questions related to dental or denture-related problems and benign and malignant disease were presented in the questionnaire. The doctors have spent an average of 5 minutes to finish the survey. The data was analyzed using descriptive statistics. Out of 130 General Practitioners 71 were well versed about plaque and calculus, whereas 86% felt that referral of the patient to a dentist is the more appropriate way to treat a dental abscess. The results of the study show that general practitioners had good dental knowledge. They were well aware about most of the dental conditions, along with the various oral manifestations of systemic diseases, and life threatening conditions. It is essential that the general practitioners should keep their knowledge updated with time. Oral health education can be included in the medical curriculum to emphasize a positive attitude towards oral health.